2009
DOI: 10.1186/1743-8462-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Medical decision making for patients with Parkinson disease under Average Cost Criterion

Abstract: Parkinson's disease (PD) is one of the most common disabling neurological disorders and results in substantial burden for patients, their families and the as a whole society in terms of increased health resource use and poor quality of life. For all stages of PD, medication therapy is the preferred medical treatment. The failure of medical regimes to prevent disease progression and to prevent long-term side effects has led to a resurgence of interest in surgical procedures. Partially observable Markov decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Evaluations of surgical options Diagnostic evaluations Lindgren et al [24] Smala et al [29] Hudry et al [32] Haycox et al [36] Findley et al [43] Kristiansen et al [47] Goulionis and Vozikis [49] Hjelmgren et al [50] Antonini et al [55] Van Laere et al [58] Dodel et al [62] Context (2) sensitivity analyses performed, the authors concluded robust results, although cost-effectiveness measures were not shown. Smala et al [29] presented a Markov model based on the progression of PD.…”
Section: Evaluations Of Drug Treatmentmentioning
confidence: 91%
See 4 more Smart Citations
“…Evaluations of surgical options Diagnostic evaluations Lindgren et al [24] Smala et al [29] Hudry et al [32] Haycox et al [36] Findley et al [43] Kristiansen et al [47] Goulionis and Vozikis [49] Hjelmgren et al [50] Antonini et al [55] Van Laere et al [58] Dodel et al [62] Context (2) sensitivity analyses performed, the authors concluded robust results, although cost-effectiveness measures were not shown. Smala et al [29] presented a Markov model based on the progression of PD.…”
Section: Evaluations Of Drug Treatmentmentioning
confidence: 91%
“…Goulionis and Vozikis, [49] Greece (independent study) Hjelmgren et al, [50] Sweden (independent study)…”
Section: Evaluations Of Surgical Optionsmentioning
confidence: 98%
See 3 more Smart Citations